GAMBARAN FAKTOR RESIKO TERJADINYA HIPERTENSI DI WILAYAH KOTA GORONTALO - Lamangida, Sri Yuningsi; Maria Masi, Gresty Natalia; Renteng, Septriani (JURNAL KEPERAWATAN, 2024)
Background: Hypertension is a cardiovascular disease and is the most prevalent health issue in society. It is often referred to as "The Silent Killer" because it frequently occurs without noticeable symptoms. The exact causes of hypertension remain uncertain to date. However, there are two risk factors contributing to hypertension: non-modifiable and modifiable risk factors. Objective: This research aims to provide an overview of the risk factors for hypertension in the Gorontalo city area. Method: This study utilizes a descriptive research approach with a sample size of 110 respondents selected through non-probability sampling, specifically purposive sampling. Results: The majority of hypertensive patients are aged 56-65 years (44.5%), female (62.7%), with a family history of hypertension (82.7%), non-smokers (55.5%), classified as obese (53.6%), and not engaging in physical activity (70.9%). Conclusion: Based on the research findings, it can be concluded that factors such as age, gender, family history, obesity, and physical activity play a role in the occurrence of hypertension in the Gorontalo city area. Keywords: Hypertension; Age; Gender; Family History; Obesity.